Respiratory epithelial adenomatoid hamartoma presenting as a mass in nasal cavity: a case report - Suraneni, Visweswara Rao; Gaddipati, Vineela; Allena, Anusha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
This article aims to report a rare case of respiratory epithelial adenomatoid hamartoma (REAH) arising from nasal septum that initially presented as bilateral sino nasal polyposis. A 45 years old male presented with a complaint of bilateral nasal obstruction for the past 3 years which was progressive and was planned for functional endoscopic sinus surgery. Polypoidal tissue was found to be coming from nasal septum intraoperatively. Histopathological examination confirmed the presence of REAH. This case demonstrates the rare presentation of REAH, clinically presented as sino nasal polyposis and confirmed as REAH by histopathological examination.